Anthocyanins in goat diets: A Review - Charoenphun, Narin; Srisaikham, Supreena; Paengkoum, Pramote; Liang, Juan Boo; Xingzhou, Tian (Agriculture and Natural Resources, 2025)
Anthocyanins are common in fruits (especially berries), vegetables, grains and purple- or red-colored flowers. They have antioxidant properties and thus play a role in preventing or reducing the risk of chronic disorders such as cardiovascular disease, cancer and diabetes. Anthocyanin-containing plants included in the diet of goats increased the anthocyanin content of milk, which adds value by providing functional benefits for consumers’ health. In addition, they improved growth performance and meat quality and prevented lipid oxidation by promoting the antioxidant status and elevating the proportions of polyunsaturated fatty acids in the muscle or superoxide dismutase activity. However, anthocyanin concentration is plant type-specific. Therefore, it is necessary to further investigate the nutritional values and anthocyanin levels of plant materials for application in the diets of ruminants, including goats, and anthocyanin persistence in the fresh and processed milk or meat. Importance of the work: Anthocyanin-rich plants have considerable potential for use as natural antioxidants in meat or dairy goat diets. Objectives: To gather insights into the role of anthocyanins in goat nutrition, contributing to future research and sustainable goat production. Materials and Methods: A systematic approach was adopted, including defining the scope, searching appropriate databases and keywords, selecting reliable and up-to-date references, collecting and organizing data in a structured manner and synthesizing the collected data. Results: Anthocyanin is a pigment present in the flavonoid compounds commonly found in plants, with antioxidant effects that are beneficial to ruminant animals and human health. Anthocyanin-rich plants have considerable potential for use as natural antioxidants in meat or dairy goat diets, since they can: 1) improve the proportions of polyunsaturated fatty acids in muscle; 2) reduce oxidative stress; 3) reduce methanogenic bacteria and improve rumen fermentation; 4) enhance superoxide dismutase; and 5) enhance the anthocyanin composition in the milk. Main finding: The use of anthocyanin-rich plants in goat diets can have a positive impact on goat health and increase production, enabling them to produce functional dairy products or meat that is beneficial for consumer health.